Olhares queer sobre o jornalismo: as representações das dissidências sexuais e de gênero no jornal O Povo - Jeronimo, Francisco Rafael Mesquita (2021)
This dissertation analyzes, from a queer look at the discursive practice of the newspaper O Povo, the representations produced about sexual and gender dissidences in contemporary journalism, in order to investigate the conceptions produced and reflected in the concrete elements of language and thus measuring the extent to which the periodical, in its informative and opinionated layer, contributes to the repetition, conservation, transformation or resignification of the patterns of inequality imposed on the group of people who live beyond the margins of the cisgender and heterosexual code. This study is based mainly on theoretical assumptions elaborated by Queer and Gender Studies, according to Lauretis (1994), Louro (2000), Butler (2000; 2017; 2019), Preciado (2011) and Bento (2014); Journalism Studies, especially through Tuchman (1999), Traquina (2005) and Silva (2010); and the Critical Discourse Analysis, having as references the works of van Leeuwen (1996), Fairclough (2001) and Resende and Ramalho (2011). Through three-dimensional observation - text, discourse practice and social practice - we confirm the hypothesis that the discourses published in the newspaper, in general, have a democratic appearance, but end up expressing an impersonalized and generalized pattern of identity presentation resistance to the cisheteronormative project – which happens above all in the argumentative range of the periodical, but which is also considerable in the informative field. We also point out that the invisibility of non-normative voices is recurrent, as well as the passivation and subjection of these subjectivities in the narrative of the newspaper's most traditional editorials, including the sections Cidades, Politics (and its variations) and Opinion; while subversive and insurgent “performativities” cross the prevailing logic and “transfer” the culture and entertainment sector of the publication. Finally, it is added that the logic of the presentation of the agenda reproduces, for the most part, the commonplace pattern of journalism, that is, it moves away from an enlightening discussion of the dynamics that produce inequalities related to gender and sexuality, and also still it is not predominantly involved by regionality markers. KEYWORDS: Journalism; Representation; Performativity; Sexual and gender dissent; Queer.